Bidirectional Non-Filamentary RRAM as an Analog Neuromorphic Synapse, Part I: Al/Mo/Pr0.7Ca0.3MnO3 Material Improvements and Device Measurements - Kibong Moon (IEEE, 2018)
We report on material improvements to non-filamentary RRAM devices based on Pr0.7Ca0.3MnO3 by introducing an MoOx buffer layer together with a reactive Al electrode, and on device measurements designed to help gauge the performance of these devices as bidirectional analog synapses for on-chip acceleration of the backpropagation algorithm. Previous Al/PCMO devices exhibited degraded LRS retention due to the low activation energy for oxidation of the Al electrode, and Mo/PCMO devices showed low conductance contrast. To control the redox reaction at the metal/PCMO interface, we introduce a 4-nm interfacial layer of conducting MoOx as an oxygen buffer layer. Due to the controlled redox reaction within this Al/Mo/PCMO device, we observed improvements in both retention and conductance on/off ratio. We confirm bidirectional analog synapse characteristics and measure “jump-tables” suitable for large scale neural network simulations that attempt to capture complex and stochastic device behavior [see companion paper]. Finally, switching energy measurements are shown, illustrating a path for future device research toward smaller devices, shorter pulses and lower programming voltages.